Imipramine Protects against Bone Loss by Inhibition of Osteoblast-Derived Microvesicles - Deng, Lili (Int J Mol Sci, 2017)
The maintenance of bone homeostasis is largely dependent upon cellular communication between osteoclasts and osteoblasts. Microvesicles (MVs) represent a novel mechanism for osteoblasts and osteoclasts communication, as has been demonstrated in our previous study. Sphingomyelinases catalyze the hydrolysis of sphingomyelin, which leads to increased membrane fluidity and facilitates MV generation. This effect can be inhibited by imipramine, an inhibitor of acid sphingomyelinase (ASM), which is also known as a member of tricyclic antidepressants (TCAs). A recent study has reported that in vitro treatment of imipramine blocked MVs release from glial cells. However, whether imipramine has this effect on osteoblast-derived MVs and whether it is involved in MV generation in vivo is unclear. Here, our investigations found that imipramine slightly reduced the expression of osteoblast differentiation of related genes, but did not impact parathyroid hormone (PTH) regulation for these genes and also did not affect receptor activator of nuclear factor-κB ligand (RANKL)-mediated osteoclast formation; however, imipramine treatment blocked MVs released from osteoblasts and inhibited MV-induced osteoclast formation. In vivo, mice administrated with imipramine were protected from ovariectomy-induced bone loss as evaluated by various bone structural parameters and serum levels of biochemical markers. Our results suggest that inhibiting the production of MVs containing RANKL in vivo is very important for preventing bone loss.